Excision of choledochal cyst in children by Roux-en-Y hepaticojejunostomy - Hossain, A. K. M. Zahid; Hasan, Gazi Zahirul; Mandal, Susankar Kumar; Koirala, Dinesh Prasad; Sah, Sanjay Kumar; Chowdhury, Razib Ahmed (Bangabandhu Sheikh Mujib Medical University Journal, 2017)
The aim of this study was to review our experience of total excision with Roux-en-Y hepatico-jejunostomy for the surgical management of type I and type IVa choledochal cysts in 30 children. Among them, 22 were in type I and 8 in type IVa choledochal cysts. All had complete excision and Roux-en-Y hepaticojejunostomy with no morality. Morbidity consisted of prolong drainage (n=2) and late onset cholangitis/pancreatitis (n=4). Choledochal cyst generally has an excellent prognosis with early complete excision and Roux-en-Y hepaticojejunostomy.